On the feasibility of monitoring the content of phenolic compounds in transformer oil - M. N. Lyutikova; S. V. Nekhoroshev; V. M. Muratova; P. R. Semenyuk; A. S. Gadzhiyeva (Омский научный вестник)
It is known that in order to restrain the process of oxidation of transformer oil, and, accordingly, to extend its service life, an antioxidant additive ionol is added to it. Previously, specialists using the method of chromato-mass spectrometry established the fact of the formation of new phenolic compounds in oil along with the consumption of the inhibitory additive ionol, namely, 2,6-di-tert-butylphenol (2,6-DTBP) and 2, 6-di-tert-p-benzoquinone. These phenolic compounds, as well as ionol, belong to the class of sterically hindered phenols, which, in turn, are able to inhibit the oxidation of oil during its operation in oil-filled transformer equipment, in particular, power transformers and current transformers. This article presents results showing that as ionol is consumed, 2,6-di-tert-butylphenol accumulates in oil from transformers. To the greatest extent, this trend is noticeable for current transformers equipped with air-drying filters (the so-called "free breathing"). The formation of 2,6-DTBP in oil can serve as an indicator of accelerated aging of the oil as a result of its prolonged contact with atmospheric oxygen. Changes in additive concentrations during oil aging are controlled using a new technique developed by us, based on IR spectroscopy.